Accelerating Innovation: Complexity, Regulation, and Temporality - Webster, Andrew (Frontiers in Sociology, 2019)
This Perspective paper explores recent moves seen in many countries towards accelerating the speed at which biomedical innovation can be delivered to the clinic. It discusses the drivers behind this and the rationale for it, illustrating this briefly in the field of regenerative medicine. It argues that the process reconfigures present/future relations, especially in terms of the relationship between different forms of evidence and risk calculations. The regulatory/innovation relationship is, as a result, being rewritten. Paradoxically, the moves towards acceleration are less to do with the arrival of a more streamlined evaluation system that selects for scientifically robust technologies ready for ‘the market’. In contrast, it reflects the growing complexity of innovation itself: whereas Latour (1987) had argued that ‘science-in the-making’ was backstage in contrast to ‘ready-made science’, the former is now very visible. This in turn has generated two other parallel process – ‘regulation-in-the-making’ and ‘risk-in-the-making’. Such shifts can be seen in the field of regenerative medicine. The paper asks how best to engage with the move towards acceleration and thereby the future oversight of innovation.